ANALISIS PENGARUH KEBUDAYAAN, SOSIAL, PRIBADI DAN PSIKOLOGIS KONSUMEN USIA MUDA TERHADAP KEPUTUSAN PEMBELIAN MAKANAN CEPAT SAJI MCDONALD’S (Studi pada konsumen McDonald’s Watugong Malang) - Okkysantria, Dyca; Hendrawan, Dimas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to determine : the influence of cultural , social , personal and psychological young consumers on purchasing decisions McDonald 's fast food either partially , simultaneously and dominant . This research is a quantitative study. In this study, the population is all consumers of fast food at McDonald's Watugong Malang younger. The sampling technique was conducted with a purposive sampling method. Data collection techniques in this study was conducted in January 2014 using a questionnaire. Validity of the instrument is calculated by Product Moment correlation. Reliability calculated by Cronbach alpha coefficients. Analysis using multiple regression analysis. The results showed that :( 1 ) Cultural factors have a positive influence on purchase decisions fast food McDonald 's,Â ( 2 ) Social factors have a positive influence on purchase decisions fast food McDonald 's,( 3 ) Personal factors have a positive influence on the purchase decisions of food McDonald's fast food, ( 4 ) psychological factors have a positive influence on purchase decisions fast food McDonald 's, ( 5 ) cultural factors, social, personal and psychological influence on purchase decisions fast food McDonald's with a contribution of 67.5 % and a variable is the dominant psychological. Keywords: Cultural Factors, Social, Personal, Psychology, Purchase decisions